Detection of early stage changes associated with adipogenesis using Raman spectroscopy under aseptic conditions. (6th October 2015) - Mitchell, Adam; Ashton, Lorna; Yang, Xuebin B.; Goodacre, Royston; Smith, Alistair; Kirkham, Jennifer
Abstract There is growing interest in the development of methods capable of non‐invasive characterization of stem cells prior to their use in cell‐based therapies. Raman spectroscopy has previously been used to detect biochemical changes commensurate with the osteogenic, cardiogenic, and neurogenic differentiation of stem cells. The aim of this study was to characterize the adipogenic differentiation of live adipose derived stem cells (ASCs) under aseptic conditions. ASCs were cultured in adipogenic or basal culture medium for 14 days in customized culture flasks containing quartz windows. Raman spectra were acquired every 3 days. Principal component analysis (PCA) was used to identify spectral changes in the cultures over time. Adipogenic differentiation was confirmed using quantitative reverse transcription polymerase chain reaction for the marker genes PPARγ and ADIPOQ and Oil red O staining performed. PCA demonstrated that lipid associated spectral features varied throughout ASC differentiation with the earliest detection of the lipid associated peak at 1, 438 cm−1 after 3 days of induction. After 7 days of culture there were clear differences between the spectra acquired from ASCs in adipogenic or basal culture medium. No changes were observed in the spectra acquired from undifferentiated ASCs. Significant up‐regulation in the expression of both PPARγ and ADIPOQ genes (P < 0.001) was observed after 14 days of differentiation as was prominent Oil red O staining. However, the Raman sampling process resulted in weaker gene expression compared with ASCs that had not undergone Raman analysis. This study demonstrated that Raman spectroscopy can be used to detect biochemical changes associated with adipogenic differentiation in a non‐invasive and aseptic manner and that this can be achieved as early as three days into the differentiation process. © 2015 The Authors. Published by Wiley Periodicals, Inc. on behalf of the International Society for Advancement of Cytometry.